Forecasting COVID-19 Pandemic in India and its Impact on Planet, People and Profit (International Journal of Scientific Research and Management (IJSRM), 2020)
The outbreak of coronavirus disease 2019 (COVID-19) has created a global health crisis that has had a deep impact on humanity. Due to the increasing number of daily cases it is a necessity to develop a prediction method. This paper aims at predicting the number of Coronavirus cases in India ahead of a month and also predicting individually some specific states/UT of India. Gated Recurrent Unit (GRU) and Facebook Prophet are used for prediction. GRU is used to show the accuracy of the neural network model and Facebook Prophet is used to predict the cases. At last the paper will elucidate the indirect effects of lockdown in India. This section will shed light on the indirect effects of the lockdown on people, planet and profit during the lockdown period taking account of the situation in India. This detailed annotation will build a foundation for the people of India to be prepared for upcoming days.